Topographic signatures and manipulations of Fe atoms, CO molecules and NaCl islands on superconducting Pb(111) - Drechsel, Carl; D’Astolfo, Philipp; Liu, Jung-Ching; Glatzel, Thilo; Pawlak, Rémy; Meyer, Ernst (Beilstein Journal of Nanotechnology, 2022)
Topological superconductivity emerging in one- or two-dimensional hybrid materials is predicted as a key ingredient for quantum computing. However, not only the design of complex heterostructures is primordial for future applications but also the characterization of their electronic and structural properties at the atomic scale using the most advanced scanning probe microscopy techniques with functionalized tips. We report on the topographic signatures observed by scanning tunneling microscopy (STM) of carbon monoxide (CO) molecules, iron (Fe) atoms and sodium chloride (NaCl) islands deposited on superconducting Pb(111). For the CO adsorption a comparison with the Pb(110) substrate is demonstrated. We show a general propensity of these adsorbates to diffuse at low temperature under gentle scanning conditions. Our findings provide new insights into high-resolution probe microscopy imaging with terminated tips, decoupling atoms and molecules by NaCl islands or tip-induced lateral manipulation of iron atoms on top of the prototypical Pb(111) superconducting surface.
Keywords: carbon monoxide (CO); lateral manipulation; NaCl; scanning tunneling microscopy; superconductivity

(untitled) - Nayak, C.; Simon, S. H.; Stern, A.; Freedman, M.; Das Sarma, S. (Rev. Mod. Phys., 2008)

(untitled) - Sato, M.; Ando, Y. (Rep. Prog. Phys., 2017)

(untitled) - Frolov, S. M.; Manfra, M. J.; Sau, J. D. (Nat. Phys., 2020)

(untitled) - Majorana, E. (Nuovo Cim., 1937)

(untitled) - Kitaev, A. Y. (Phys.-Usp., 2001)

(untitled) - Alicea, J. (Rep. Prog. Phys., 2012)

(untitled) - Wang, Z.; Rodriguez, J. O.; Jiao, L.; Howard, S.; Graham, M.; Gu, G. D.; Hughes, T. L.; Morr, D. K.; Madhavan, V. (Science, 2020)

(untitled) - Lutchyn, R. M.; Bakkers, E. P. A. M.; Kouwenhoven, L. P.; Krogstrup, P.; Marcus, C. M.; Oreg, Y. (Nat. Rev. Mater., 2018)

(untitled) - Mourik, V.; Zuo, K.; Frolov, S. M.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Science, 2012)

(untitled) - Nadj-Perge, S.; Drozdov, I. K.; Bernevig, B. A.; Yazdani, A. (Phys. Rev. B, 2013)

(untitled) - Pientka, F.; Glazman, L. I.; von Oppen, F. (Phys. Rev. B, 2013)

(untitled) - Klinovaja, J.; Stano, P.; Yazdani, A.; Loss, D. (Phys. Rev. Lett., 2013)

(untitled) - Nadj-Perge, S.; Drozdov, I. K.; Li, J.; Chen, H.; Jeon, S.; Seo, J.; MacDonald, A. H.; Bernevig, B. A.; Yazdani, A. (Science, 2014)

(untitled) - Ruby, M.; Pientka, F.; Peng, Y.; von Oppen, F.; Heinrich, B. W.; Franke, K. J. (Phys. Rev. Lett., 2015)

(untitled) - Pawlak, R.; Kisiel, M.; Klinovaja, J.; Meier, T.; Kawai, S.; Glatzel, T.; Loss, D.; Meyer, E. (npj Quantum Inf., 2016)

(untitled) - Kim, H.; Palacio-Morales, A.; Posske, T.; Rózsa, L.; Palotás, K.; Szunyogh, L.; Thorwart, M.; Wiesendanger, R. (Sci. Adv., 2018)

(untitled) - Jäck, B.; Xie, Y.; Li, J.; Jeon, S.; Bernevig, B. A.; Yazdani, A. (Science, 2019)

(untitled) - Palacio-Morales, A.; Mascot, E.; Cocklin, S.; Kim, H.; Rachel, S.; Morr, D. K.; Wiesendanger, R. (Sci. Adv., 2019)

(untitled) - Fu, L.; Kane, C. L. (Phys. Rev. Lett., 2008)

(untitled) - Sun, H.-H.; Zhang, K.-W.; Hu, L.-H.; Li, C.; Wang, G.-Y.; Ma, H.-Y.; Xu, Z.-A.; Gao, C.-L.; Guan, D.-D.; Li, Y.-Y.; Liu, C.; Qian, D.; et al. (Phys. Rev. Lett., 2016)

(untitled) - Zhang, P.; Yaji, K.; Hashimoto, T.; Ota, Y.; Kondo, T.; Okazaki, K.; Wang, Z.; Wen, J.; Gu, G. D.; Ding, H.; Shin, S. (Science, 2018)

(untitled) - Zhu, S.; Kong, L.; Cao, L.; Chen, H.; Papaj, M.; Du, S.; Xing, Y.; Liu, W.; Wang, D.; Shen, C.; Yang, F.; Schneeloch, J.; et al. (Science, 2020)

(untitled) - Kezilebieke, S.; Huda, M. N.; Vaňo, V.; Aapro, M.; Ganguli, S. C.; Silveira, O. J.; Głodzik, S.; Foster, A. S.; Ojanen, T.; Liljeroth, P. (Nature, 2020)

(untitled) - Eigler, D. M.; Schweizer, E. K. (Nature, 1990)

(untitled) - Stroscio, J. A.; Eigler, D. M. (Science, 1991)

(untitled) - Zeppenfeld, P.; Lutz, C. P.; Eigler, D. M. (Ultramicroscopy, 1992)

(untitled) - Langewisch, G.; Falter, J.; Fuchs, H.; Schirmeisen, A. (Phys. Rev. Lett., 2013)

(untitled) - Pawlak, R.; Kawai, S.; Meier, T.; Glatzel, T.; Baratoff, A.; Meyer, E. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Kawai, S.; Koch, M.; Gnecco, E.; Sadeghi, A.; Pawlak, R.; Glatzel, T.; Schwarz, J.; Goedecker, S.; Hecht, S.; Baratoff, A.; Grill, L.; Meyer, E. (Proc. Natl. Acad. Sci. U. S. A., 2014)

(untitled) - Kawai, S.; Benassi, A.; Gnecco, E.; Söde, H.; Pawlak, R.; Feng, X.; Müllen, K.; Passerone, D.; Pignedoli, C. A.; Ruffieux, P.; Fasel, R.; Meyer, E. (Science, 2016)

(untitled) - Stroscio, J. A.; Celotta, R. J. (Science, 2004)

(untitled) - Khajetoorians, A. A.; Wegner, D.; Otte, A. F.; Swart, I. (Nat. Rev. Phys., 2019)

(untitled) - Bartels, L.; Meyer, G.; Rieder, K.-H. (Appl. Phys. Lett., 1997)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Gross, L. (Nat. Chem., 2011)

(untitled) - Feldman, B. E.; Randeria, M. T.; Li, J.; Jeon, S.; Xie, Y.; Wang, Z.; Drozdov, I. K.; Andrei Bernevig, B.; Yazdani, A. (Nat. Phys., 2017)

(untitled) - Kamlapure, A.; Cornils, L.; Wiebe, J.; Wiesendanger, R. (Nat. Commun., 2018)

(untitled) - Pawlak, R.; Ouyang, W.; Filippov, A. E.; Kalikhman-Razvozov, L.; Kawai, S.; Glatzel, T.; Gnecco, E.; Baratoff, A.; Zheng, Q.; Hod, O.; Urbakh, M.; Meyer, E. (ACS Nano, 2016)

(untitled) - Heinrich, B. W.; Braun, L.; Pascual, J. I.; Franke, K. J. (Nat. Phys., 2013)

(untitled) - Heinrich, B. W.; Braun, L.; Pascual, J. I.; Franke, K. J. (Nano Lett., 2015)

(untitled) - Repp, J.; Meyer, G.; Stojković, S. M.; Gourdon, A.; Joachim, C. (Phys. Rev. Lett., 2005)

(untitled) - Hirjibehedin, C. F.; Lutz, C. P.; Heinrich, A. J. (Science, 2006)

(untitled) - Repp, J.; Steurer, W.; Scivetti, I.; Persson, M.; Gross, L.; Meyer, G. (Phys. Rev. Lett., 2016)

(untitled) - Meier, T.; Pawlak, R.; Kawai, S.; Geng, Y.; Liu, X.; Decurtins, S.; Hapala, P.; Baratoff, A.; Liu, S.-X.; Jelínek, P.; Meyer, E.; Glatzel, T. (ACS Nano, 2017)

(untitled) - Pawlak, R.; Vilhena, J. G.; D’Astolfo, P.; Liu, X.; Prampolini, G.; Meier, T.; Glatzel, T.; Lemkul, J. A.; Häner, R.; Decurtins, S.; Baratoff, A.; Pérez, R.; et al. (Nano Lett., 2020)

(untitled) - Pawlak, R.; Drechsel, C.; D’Astolfo, P.; Kisiel, M.; Meyer, E.; Cerda, J. I. (Proc. Natl. Acad. Sci. U. S. A., 2020)

(untitled) - Giessibl, F. J. (Rev. Mod. Phys., 2003)

(untitled) - Nečas, D.; Klapetek, P. (Cent. Eur. J. Phys., 2012)

(untitled) - Chang, S. H.; Su, W. B.; Jian, W. B.; Chang, C. S.; Chen, L. J.; Tsong, T. T. (Phys. Rev. B, 2002)

(untitled) - Jeffrey, C. A.; Conrad, E. H.; Feng, R.; Hupalo, M.; Kim, C.; Ryan, P. J.; Miceli, P. F.; Tringides, M. C. (Phys. Rev. Lett., 2006)

(untitled) - Krupski, A. (Phys. Rev. B, 2009)

(untitled) - Schmid, M.; Hebenstreit, W.; Varga, P.; Crampin, S. (Phys. Rev. Lett., 1996)

(untitled) - Song, S. Y.; Seo, J. (Sci. Rep., 2017)

(untitled) - Auwärter, W.; Seufert, K.; Bischoff, F.; Ecija, D.; Vijayaraghavan, S.; Joshi, S.; Klappenberger, F.; Samudrala, N.; Barth, J. V. (Nat. Nanotechnol., 2012)

(untitled) - Choi, D.-J.; Rubio-Verdú, C.; de Bruijckere, J.; Ugeda, M. M.; Lorente, N.; Pascual, J. I. (Nat. Commun., 2017)

(untitled) - Fremy-Koch, S.; Sadeghi, A.; Pawlak, R.; Kawai, S.; Baratoff, A.; Goedecker, S.; Meyer, E.; Glatzel, T. (Phys. Rev. B, 2019)

(untitled) - Feng, M.; Cabrera-Sanfelix, P.; Lin, C.; Arnau, A.; Sánchez-Portal, D.; Zhao, J.; Echenique, P. M.; Petek, H. (ACS Nano, 2011)

(untitled) - Briner, B. G.; Doering, M.; Rust, H.-P.; Bradshaw, A. M. (Science, 1997)

(untitled) - Feng, M.; Lin, C.; Zhao, J.; Petek, H. (Annu. Rev. Phys. Chem., 2012)

(untitled) - Ahner, J.; Mocuta, D.; Ramsier, R. D.; Yates, J. T., Jr (J. Chem. Phys., 1996)

(untitled) - Kato, H.; Okuyama, H.; Ichihara, S.; Kawai, M.; Yoshinobu, J. (J. Chem. Phys., 2000)

(untitled) - Repp, J.; Meyer, G.; Rieder, K.-H. (Phys. Rev. Lett., 2004)

(untitled) - Schuler, B.; Persson, M.; Paavilainen, S.; Pavliček, N.; Gross, L.; Meyer, G.; Repp, J. (Phys. Rev. B, 2015)

(untitled) - Mohr, M.; Weismann, A.; Li, D.; Brandbyge, M.; Berndt, R. (Phys. Rev. B, 2021)

(untitled) - Khajetoorians, A. A.; Valentyuk, M.; Steinbrecher, M.; Schlenk, T.; Shick, A.; Kolorenc, J.; Lichtenstein, A. I.; Wehling, T. O.; Wiesendanger, R.; Wiebe, J. (Nat. Nanotechnol., 2015)

(untitled) - Hla, S.-W.; Braun, K.-F.; Rieder, K.-H. (Phys. Rev. B, 2003)

(untitled) - Hla, S.-W. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2005)

(untitled) - Bartels, L.; Meyer, G.; Rieder, K.-H. (Phys. Rev. Lett., 1997)

(untitled) - Celotta, R. J.; Balakirsky, S. B.; Fein, A. P.; Hess, F. M.; Rutter, G. M.; Stroscio, J. A. (Rev. Sci. Instrum., 2014)

(untitled) - Temirov, R.; Soubatch, S.; Neucheva, O.; Lassise, A. C.; Tautz, F. S. (New J. Phys., 2008)

(untitled) - Weiss, C.; Wagner, C.; Kleimann, C.; Rohlfing, M.; Tautz, F. S.; Temirov, R. (Phys. Rev. Lett., 2010)

(untitled) - Emmrich, M.; Huber, F.; Pielmeier, F.; Welker, J.; Hofmann, T.; Schneiderbauer, M.; Meuer, D.; Polesya, S.; Mankovsky, S.; Ködderitzsch, D.; Ebert, H.; Giessibl, F. J. (Science, 2015)